The heart disease breakthrough what even your doctor doesn't know about preventing a heart attac - Yannios, Thomas (John Wiley & Sons, 1999)
The author's ten steps involve getting blood tests, knowing individual genetic risk profiles, knowing LDL levels, knowing HDL levels, knowing Lp(a) levels, understanding blood-clotting, changing diet, losing weight, exercising, and considering the proper medication.